2022
DOI: 10.1039/d1ra09459a
|View full text |Cite
|
Sign up to set email alerts
|

Bio-based arginine surface-modified ammonium polyphosphate: an efficient intumescent flame retardant for epoxy resin

Abstract: Arginine modified ammonium polyphosphate was prepared through the cation-exchange reaction and applied as an intumescent flame retardant for epoxy resin.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 53 publications
0
19
0
Order By: Relevance
“…Moreover, the P 2p spectrum (Figure g) was split into three peaks at 132.4, 133.7, and 134.8 eV, corresponding to P–O (P–O–C, P–O–P), P–N, and PO x , respectively, which further indicated that cross-linked organophosphorus compounds (e.g., pyrophosphate, polyphosphate, phosphorus oxynitrides, etc.) were formed in the char residue of the EP/4%CNT@HBPPA@MoS 2 composite . As for the S 2p spectra (Figure i), the two peaks at 162.4 and 163.8 eV are ascribed to S 2p 3/2 and S 2p 1/2 deriving from MoS 2 nanosheets, respectively, while the other two peaks occurring at 165.3 and 169.1 eV are related to the SO 4 2– and C–S groups, respectively, due to the reaction of partial MoS 2 with oxygen or pyrolyzed fragments of epoxy chains .…”
Section: Resultsmentioning
confidence: 92%
See 2 more Smart Citations
“…Moreover, the P 2p spectrum (Figure g) was split into three peaks at 132.4, 133.7, and 134.8 eV, corresponding to P–O (P–O–C, P–O–P), P–N, and PO x , respectively, which further indicated that cross-linked organophosphorus compounds (e.g., pyrophosphate, polyphosphate, phosphorus oxynitrides, etc.) were formed in the char residue of the EP/4%CNT@HBPPA@MoS 2 composite . As for the S 2p spectra (Figure i), the two peaks at 162.4 and 163.8 eV are ascribed to S 2p 3/2 and S 2p 1/2 deriving from MoS 2 nanosheets, respectively, while the other two peaks occurring at 165.3 and 169.1 eV are related to the SO 4 2– and C–S groups, respectively, due to the reaction of partial MoS 2 with oxygen or pyrolyzed fragments of epoxy chains .…”
Section: Resultsmentioning
confidence: 92%
“…Second, the pyridine structure (N-6) was reported to be more thermally stable than the pyrrole structure (N-5); thus, more stable chemical structures were generated under the catalytic effect of Mo ions to defend the heat and oxidation reaction . For O 1s spectra (Figure f), the peak at 531.4 eV represents the double oxygen bonds in PO or CO, and the peaks at 532.4 and 533.2 eV belong to the single oxygen bonds in P–O (P–O–P, P–O–C) and C–O, respectively. , However, a small peak (530.5 eV) assigned to Mo–O occurred in the char residue of the EP/4%CNT@HBPPA@MoS 2 composite, coupled with the enhanced proportion of Mo 6+ (233.1 and 236.1 eV) appeared in the Mo 3d spectra (Figure h), ,, demonstrating the presence of MoO 3 , which was consistent with the results obtained from FTIR and XRD patterns. Moreover, the P 2p spectrum (Figure g) was split into three peaks at 132.4, 133.7, and 134.8 eV, corresponding to P–O (P–O–C, P–O–P), P–N, and PO x , respectively, which further indicated that cross-linked organophosphorus compounds (e.g., pyrophosphate, polyphosphate, phosphorus oxynitrides, etc.)…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the gas phase, PO 2 · and PO· radicals were produced with the decomposition of the DOPO group in DPM‐H, which can capture the HO· and H· radicals generated during the burning of EP to prevent the EP combustion process 68,69 . In the meantime, inflammable gases such as CO 2 , H 2 O, and NH 3 are produced with the decomposition of APP, which can dilute the oxygen content around the EP 70 . Therefore, the presence of DPM‐H and APP in EP made the flame‐retardant EP achieve good flame retardancy.…”
Section: Resultsmentioning
confidence: 99%
“…68,69 In the meantime, inflammable gases such as CO 2 , H 2 O, and NH 3 are produced with the decomposition of APP, which can dilute the oxygen content around the EP. 70 Therefore, the presence of DPM-H and APP in EP made the flame-retardant EP achieve good flame retardancy.…”
Section: Flame-retardant Mechanism Analysismentioning
confidence: 99%